Biodiesel Hasil Transesterifikasi Minyak Biji Nyamplung (Calophyllum inophyllum) Dengan Metanol - Musta, Rustam; Haetami, Aceng; Salmawati, Mimi (Indonesian Journal of Chemical Research, 2017)
Study of the transesterification of Calophyllum innophyllum seed oil from Kendari with methanol has been conducted. The purpose of the research to determine of the yield of ester produced in transesterification process with methanol, the viscosity of biodiesel produced, moisture content of biodiesel produced, density of biodiesel produced. The methods used in this study are sample preparation, transesterification process, biodiesel quality parameter test consisting of viscosity, moisture content and density. The results showed that good concentration of phosphoric acid was used to remove the gum is 85%, the yield of ester produced in the process of transesterification with methanol is 111,647%, parameter of biodiesel quality measured that viscosity = 0,315 mm2/ s not fulfill Indonesian National Standart (INS), water content is 0.02 meets the INS and the density = 0.8725 g / cm3 meets the INS standard